2005
DOI: 10.1161/circulationaha.105.566190
|View full text |Cite
|
Sign up to set email alerts
|

Hypercholesterolemia Abrogates Late Preconditioning via a Tetrahydrobiopterin-Dependent Mechanism in Conscious Rabbits

Abstract: Background-Although the late phase of ischemic preconditioning (PC) is known to confer cardioprotection in healthy animal models, it is unknown whether this phenomenon exists in the presence of hypercholesterolemia. The goal of this study was to determine whether the infarct-sparing effect of late PC is affected by hypercholesterolemia and, if so, whether a tetrahydrobiopterin (BH 4 )-dependent mechanism is responsible for the loss of late PC. Methods and Results-Conscious rabbits fed a normal diet or a 1% cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 36 publications
4
49
0
1
Order By: Relevance
“…However, the bacterial endotoxin analog monophosphoryl lipid A-induced late protection in the same rabbit model remained unaffected by experimental hyperlipidemia and atherosclerosis (Szilvassy et al, 1998). The loss of the infarct size-limiting effect of late preconditioning in another conscious rabbit model of coronary occlusion and reperfusion was shown by Tang et al (2005). The loss of NO donor-induced late preconditioning was shown in the same rabbit model by the same group (Tang et al, 2004).…”
Section: Cardioprotection By Pre-and Postconditioning In Hyperlipidemiamentioning
confidence: 92%
See 1 more Smart Citation
“…However, the bacterial endotoxin analog monophosphoryl lipid A-induced late protection in the same rabbit model remained unaffected by experimental hyperlipidemia and atherosclerosis (Szilvassy et al, 1998). The loss of the infarct size-limiting effect of late preconditioning in another conscious rabbit model of coronary occlusion and reperfusion was shown by Tang et al (2005). The loss of NO donor-induced late preconditioning was shown in the same rabbit model by the same group (Tang et al, 2004).…”
Section: Cardioprotection By Pre-and Postconditioning In Hyperlipidemiamentioning
confidence: 92%
“…A decrease in cardiac NO bioavailability due to increased nitrosative stress (Hoshida et al, 1996;Ferdinandy et al, 1997;Csonka et al, 2001;Tang et al, 2005; CARDIOPROTECTION AND RISK FACTORS for reviews, see Ferdinandy and Schulz, 2003;Pacher et al, 2007) and resulting activation of matrix metalloproteinases increased ecto-5Ј-nucleotidase activity (Ueda et al, 1999), as well as enhanced apoptotic cell death via the caspase-1 cascade , have been shown to contribute to increased ischemia/reperfusion injury and loss of classic preconditioning in hyperlipidemic animal models. Interestingly, inhibition of the mevalonate pathway by hyperlipidemia has been also described as a possible mechanism of the lost cardioprotection because mevalonate restored the effect of preconditioning on postischemic myocardial function and lactate dehydrogenase release in hyperlipidemic rats .…”
Section: Interaction Of Hyperlipidemia and Antihyperlipidemic Statinsmentioning
confidence: 99%
“…For studies of ischemic preconditioning, initially we used a protocol of six 4-min occlusion/4-min reperfusion cycles [the same protocol we have used in our previous studies in conscious rabbits (20,23,25) and in open-chest mice (9, 10)]. We tested this protocol in four conscious rats and found that all four animals developed ventricular fibrillation upon reperfusion after the first 4-min coronary occlusion.…”
Section: Methodsmentioning
confidence: 99%
“…This also applies to late preconditioning (199) and postconditioning (73). In fact, the same rabbit in the ischemia-reperfusion model was used to show the loss of the infarct limitation in response to late preconditioning (204).…”
Section: Comorbidities and Cardioprotection: Prevailing Knowledge Intmentioning
confidence: 99%